Santri Resilience in Countering Religious Extremism: Evidence from Pesantren Education in Indonesia - Vita Fitriatul Ulya; Moh Abdulloh Hilmi; Achmad Muhibbin Zuhri; Herfin Fahri; Vacharee Dedduang (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study examines how pesantren education strengthens santri’s resilience against extremist narratives in the digital era. Previous studies have highlighted pesantren’s role in promoting religious moderation and preventing radicalism. However, the psychopedagogical processes through which resilience against extremist ideologies is internalized at the individual level have received limited attention. Hence, this study investigates how character formation, emotional development, and critical religious understanding contribute to resilience-building within pesantren education. Pondok Pesantren Manbail Futuh Jenu Tuban, Indonesia, was selected for this qualitative case study design. The data were collected through in-depth interviews, participatory observation, and documentation. The thematic analysis is employed, involving coding, categorization, and theme development. The findings reveal that santri’s resilience against extremist narratives is intensified through psychopedagogical approaches embedded in pesantren activities, including halaqah discussions, mentoring, muhâsabah activities, informal counselling, and critical reflection on digital religious content. These practices foster critical awareness, emotional regulation, moral reasoning, and moderate religious perspectives. However, social media exposure, uncontrolled information flows, and emotional vulnerability remain significant challenges in shaping santris’ morality, social learning, and resilience theory within the pesantren context. It demonstrates that resilience against religious extremism is the results of various factors i.e. doctrinal instruction and the interaction of cognitive, emotional, social, and spiritual dimensions of education. These findings highlight the importance of integrating digital literacy, reflective learning, and emotional mentoring into contemporary character education programs to prevent religious extremism among Muslim youth. Accordingly, this study contributes to Islamic education discourse and resilience theory. It confirms that resilience against extremism is established through the psychopedagogical process in pesantren routine, in addition to religious doctrine transmission.